Splice-site and Frameshift Mutations of β-Globin Gene Found in Thalassemia Carrier Screening in Yogyakarta Special Region, Indonesia - Niken Satuti Nur Handayani; Nailil Husna; Gunawan Rahmil; Riris Anindya Ghifari; Lily Widyawati; Indra Lesmana (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: β-thalassemia is an inherited blood disorder that relatively common in Southeast Asian countries. In Indonesia, it is estimated that 200,000 infants with thalassemia carrier born each year. Mutation causing β-thalassemia is highly varied and relatively specific in a population. This study aimed to identify the mutations responsible for β-thalassemia from Thalassemia Carrier Screening conducted in Yogyakarta Special Region. This information is beneficial for developing a strategic prevention program to control thalassemia in the region.METHODS: Twenty-eight blood samples of haematologically suspected β-thalassemia from participant of thalassemia screening program in Yogyakarta Special Region were investigated for β-globin gene mutation by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), amplification refractory mutation system (ARMS) and DNA sequencing.RESULTS: Our samples showed average HbA2 value of 5±0.81% and HbF value of 2±2.29%. It showed eight abnormal erythrocyte morphologies dominated by hypochromia (96.4%), cigar cell (85.7%), and microcytosis (78.6%). Our molecular investigation identified three splice-site mutations namely InterVening Sequence (IVS)-1-5 (G>C) (71.4%), IVS-1-2 (T>C) (7.1%), and IVS-1-1 (G>T) (3.6%), two frameshift mutations that are CD35 (-C) (10.7%) and CD8/9 (+G) (3.6%), and a missense mutation of CD6 (GAG>GTG) (3.6%).CONCLUSION: Our study concluded on a high prevalence of IVS-1-5 (G>C) mutation in Yogyakarta Special Region. This mutation information is significant for developing a strategic prevention program to control thalassemia in the region, for example for developing a rapid molecular test for future screening program.KEYWORDS: β-Globin gene, thalassemia, screening, carrier, mutation, Yogyakarta